Klasifikasi Penyebaran Covid-19 Menggunakan Algoritma C4.5 di Kecamatan Medan Helvetia - Ginting, Riah Ukur; Harefa, Mirna Yanti; Rianto Sitanggang; Immanuel H G Manurung (Universitas Sari Mutiara Indonesia Medan, 2023)
The development of Science and Technology currently plays an important role in companies and government agencies in providing useful information for the interests of operations and management. Therefore, many companies or government agencies have information technology departments or information systems. Likewise UPT. The Helvetia District Health Center, namely in processing and classifying the spread of Covid-19, must use an information system in order to support activities in handling the spread of the corona virus, especially in the Medan Helvetia District. In this study, a classification system was built to classify the spread of Covid-19 using the C4.5 Algorithm. The development of this system uses the PHP programming language with a MySQL database. The results obtained in the test by applying the C4.5 Algorithm then obtained an Accuracy of 0.859, so that with this system it is expected that the Covid-19 handling task force at UPT. The Helvetia District Health Center can classify the spread of Covid-19 in the Medan Helvetia District to be more efficient and effective.